The Role of Technology in The Development of Sex Tourism in Lokasari Mangga Besar West Jakarta - Gabriel Wirawan Putra; Budi Setiawan (Jurnal Syntax Transformation, 2023)
Lokasari Mangga Besar itself is a place that is famous for its culinary and entertainment centers. However, the entertainment available at night is different entertainment from most of the entertainment that is popular with ordinary people and teenagers who are famous for sex tourism, such as pubs, discos, and so on. Sex tourism, such as prostitution and harmful entertainment, occurs at night in the Lokasari People's Entertainment Park (THR) area, which increases the atmosphere of life and crowds, especially at night. However, currently, in Indonesia, there is no legal basis or legislation that legalizes or covers sex tourism to this day. However, in reality, sex tourism exists in tourist areas, especially in the Mangga Besar area. Sex tourism in Mangga Besar itself has changed a lot since the pandemiccovid-19, which resulted in several shops in Lokasari closing due to the lack of visitors. They were also forced to make several innovations to market their services using existing technological developments from various applications. This research aims to obtain new information related to changes that have occurred with technological developments and their role in sex tourism at Lokasari Mangga Besar, West Jakarta. The research method that will be carried out uses a descriptive qualitative approach by collecting data through interviews and observation to obtain data information from sources in the local environment as primary data sources. The research results show that tourism marketing and operations in Mangga Besar itself vary from conventional methods to modern methods that utilize the benefits of technology. Most ways of working that use application technology have advantages in terms of income due to more efficient marketing and communication to reach more people, especially new people. The use of technology from various applications such as chat and Twitter has played quite an important role in marketing and offering services in this area.